Kebersyukuran dan Efikasi Diri sebagai Protektor Psikologis terhadap Kecemasan Masa Depan Mahasiswa - Riris Anggie Yuana; Amanda Pasca Rini; Bawinda Sri Les (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2026)
Final-year undergraduate students represent a group susceptible to future anxiety, a condition often exacerbated by a competitive job market and the inherent uncertainties individuals face about their futures. This study aimed to analyze the relationship between gratitude, self-efficacy, and future anxiety among final-year psychology students. A quantitative method was employed, utilizing a simple random sampling technique. The sample consisted of 100 final-year students from a Faculty of Psychology. Data were collected using a gratitude scale, the General Self-Efficacy Scale (GSE), and the Future Anxiety Scale (FAS). Data analysis was performed using multiple regression analysis. The results indicated a significant and negative relationship between both gratitude and self-efficacy with future anxiety. That is, higher levels of gratitude were associated with lower levels of future anxiety, and vice versa. Similarly, higher levels of self-efficacy were correlated with lower levels of future anxiety. Gratitude and self-efficacy collectively accounted for 40.4% of the variance in future anxiety, as shown by the R-square value (R2=0.404). Keywords: final-year students, future anxiety, gratitude, self-efficacy Mahasiswa akhir merupakan kelompok yang rentan mengalami kecemasan akan masa depan, hal ini disebabkan oleh ketatnya persaingan kerja dan ketidakpastian masa depan yang dimiliki setiap individu. Penelitian ini bertujuan untuk menganalisis hubungan antara kebersyukuran dan efikasi diri dengan kecemasan akan masa depan pada mahasiswa akhir di fakultas psikologi. Penelitian ini menggunakan metode kuantitatif dengan teknik simple random sampling. Sampel terdiri dari 100 mahasiswa akhir dari Fakultas Psikologi. Pengambilan data menggunakan skala kebersyukuran, skala efikasi diri (GSE), dan skala kecemasan akan masa depan (FAS). Analisis data dilakukan dengan uji regresi berganda. Hasil penelitian menunjukkan adanya hubungan yang bersifat negatif dan signifikan antara kebersyukuran dan efikasi diri dengan kecemasan akan masa depan. Artinya, semakin tinggi kebersyukuran maka akan semakin rendah kecemasan akan masa depan, begitupula sebaliknya. Semakin tinggi efikasi diri maka akan semakin rendah kecemasan akan masa depan yang dirasakan oleh individu, begitupula sebaliknya. Antara kebersyukuran dan efikasi diri bersama-sama memberikan sumbangsih sebesar 40,4% kecemasan akan masa depan, seperti yang ditunjukkan oleh nilai R-square (R2 = 0,404). Kata kunci: Efikasi diri, Kebersyukuran, Kecemasan akan masa depan, Mahasiswa tingkat akhir.